Synthesis method of aryl thermotropic liquid crystal polyester

By synthesizing aryl thermochromic liquid crystal polyester with boron-containing Lewis acid catalytic system, the problems of metal residue and alkali catalytic influence in the prior art are solved, and the synthesis and industrial continuous production of high-performance liquid crystal polyester are achieved.

CN119751829APending Publication Date: 2025-04-04NANJING UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411881505.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has the effect of metal residue or alkali catalysis on carboxylic acid monomers when preparing liquid crystal polyesters, resulting in high production costs and low yields.

Method used

Using a boron-containing Lewis acid catalytic system, aryl thermogenic liquid crystal polyester is prepared by mixing the aryl monomer raw material with a boron-containing Lewis acid catalyst, nitrogen ventilation and multi-stage heating treatment, and finally vacuum reaction is carried out at 290-350°C.

Benefits of technology

The synthesis of high-performance aryl thermochromic liquid crystal polyester is achieved, with high molecular weight, small dielectric loss, high tensile modulus, maximum tensile stress up to 180N/m2, simple operation, easy control of reaction conditions, suitable for continuous production, and will not cause pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198315720000031
    Figure BDA0005198315720000031
  • Figure BDA0005198315720000032
    Figure BDA0005198315720000032
  • Figure BDA0005198315720000041
    Figure BDA0005198315720000041
Patent Text Reader

Abstract

The invention provides a synthesis method of aryl thermotropic liquid crystal polyester, and relates to the field of polymer materials. According to the scheme, the aryl thermotropic liquid crystal polyester is synthesized by adopting a boron-containing Lewis acid catalytic system, and the boron-containing Lewis acid catalytic system adopts a boron-containing Lewis acid catalyst; the preparation method comprises the following steps: mixing an aryl monomer raw material with a boron-containing Lewis acid catalytic system, firstly introducing nitrogen into the reaction system until the reaction system is in a nitrogen atmosphere, then heating the reaction system, and finally carrying out vacuum reaction on the reaction system at 290-350 DEG C for 1-24 hours to prepare the aryl thermotropic liquid crystal polyester, the aryl thermotropic liquid crystal polyester which is small in dielectric loss, high in tensile modulus and capable of achieving the maximum tensile stress of 180 N / m < 2 > can be prepared, the synthesis process is easy to operate, reaction conditions are easy to control, and continuous production can be carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a method for synthesizing aromatic thermotropic liquid crystal polyester. Background Art

[0002] Liquid crystal polyesters are a class of high-end polymer materials with exceptional performance. Due to their unique physical and chemical properties, they are widely used in polymer materials, communications technology, electronic devices, optical components, and other fields. The development of liquid crystal materials demands increasingly higher performance. Liquid crystal polyesters, in particular, have become a research hotspot in the materials field due to their excellent mechanical and dielectric properties, processing capabilities, and high-temperature resistance.

[0003] In recent years, with the rapid development of electronics industries such as mobile data communications, industrial automation, and aerospace, the data traffic carried by the Internet of Everything has increased, placing greater demands on related electronic equipment and basic materials. Printed circuit boards (PCBs), which carry information transmission, have faced increasing challenges, from the MHz of 4G to the GHz of 5G and on to even higher frequencies in the future, as they continue to develop in the direction of high frequency, high speed, and digitalization. In the field of 5.5G and 6G communications, LCP (liquid crystal polymer) materials are particularly important in millimeter wave transmission due to their low loss properties. They far exceed PI and MPI materials and have less impact on signals, making them a necessary alternative material.

[0004] Research shows that in order to ensure high-speed information transmission and low latency, in addition to requiring low copper foil transmission loss, the PCB substrate material is also required to have low dielectric transmission loss (TLD). Dielectric transmission loss is related to frequency, board dielectric constant (Dk), and board dielectric loss (Df). It can be seen that reducing board Dk and Df can effectively reduce dielectric transmission loss and ensure high-speed signal transmission.

[0005] LCP has a low dielectric constant, low dielectric loss, and excellent overall performance, and has good application prospects. It is currently widely used in 5GHz communications. For example, research on the dielectric constant, dielectric loss, and insertion loss of liquid crystal polymers at 30-110GHz found that the dielectric constant of LCP is stable at around 3.16 and Df is less than 0.0048. Research on the PCB processing performance and insertion loss performance of LCP at 40GHz, 60GHz, and 70GHz showed that its excellent processability and low insertion loss make LCP exhibit excellent performance in display antennas. For example, existing technology uses LCP to prepare an antenna that has excellent performance at 0.51-14.4GHz. In addition, research on the performance of LCP films and SiO2 films on silicon carriers in the millimeter wave field shows that the insertion loss of LCP films is only 1 / 2 of that of SiO2 films.

[0006] When preparing liquid crystal polyester, the catalytic system is the key to the development of liquid crystal polyester towards high performance. Summary of the Invention

[0007] The present invention aims to provide a method for synthesizing aromatic thermotropic liquid crystal polyesters, which can continuously synthesize a series of high-performance liquid crystal polymers by using a boron-containing Lewis acid catalyst system.

[0008] To achieve the above object, the present invention proposes the following technical solutions: a method for synthesizing an aromatic thermotropic liquid crystal polyester, wherein the aromatic thermotropic liquid crystal polyester is synthesized using a boron-containing Lewis acid catalyst system;

[0009] The boron-containing Lewis acid catalytic system adopts a boron-containing Lewis acid catalyst, and the boron-containing Lewis acid catalyst is selected from one or more of boric acid, boric acid ester, monosubstituted aryl boronic acid, polysubstituted aryl boronic acid, monosubstituted borane, and polysubstituted borane.

[0010] Furthermore, a method for synthesizing an aromatic thermotropic liquid crystal polyester comprises mixing an aromatic monomer raw material with a boron-containing Lewis acid catalyst system, first passing nitrogen gas through the reaction system for 10 to 30 minutes, then subjecting the reaction system to a multi-stage temperature increase treatment, and finally subjecting the reaction system to a vacuum reaction at 290 to 350° C. for 1 to 24 hours to obtain the aromatic thermotropic liquid crystal polyester;

[0011] The multi-stage temperature treatment process of the reaction system is as follows: first, the temperature is raised to 160-200°C and kept for 10 min to 1 h, then the temperature is raised to 200-220°C and kept for 1 to 2 h, then the temperature is raised to 240-260°C and kept for 10 min to 1 h, and then the temperature is raised to 270-290°C and kept for 10 min to 1 h, and finally the temperature is raised to the vacuum reaction temperature.

[0012] Furthermore, the amount of the boron-containing Lewis acid catalyst in the boron-containing Lewis acid catalytic system is 0.01 to 20 wt % of the total mass of the aromatic monomer raw materials in the reaction system.

[0013] Furthermore, the aromatic monomer raw material is selected from bifunctional or multifunctional aromatic esters, aromatic acids, and aromatic alcohols.

[0014] Furthermore, the aromatic monomer raw materials are selected from two or three of the following aromatic monomers:

[0015]

[0016] Furthermore, the boron-containing Lewis acid catalyst is selected from one or more of the following boron-containing Lewis acid catalysts:

[0017]

[0018]

[0019] Furthermore, the temperature of the vacuum reaction in the reaction system is 300°C.

[0020] Furthermore, the reaction system is subjected to vacuum reaction for 6 to 12 hours.

[0021] Furthermore, the reaction system is subjected to vacuum reaction for 1 hour.

[0022] Furthermore, the mass of the aromatic monomer raw material in the reaction system is 1 to 200 g.

[0023] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects:

[0024] The present invention discloses a method for synthesizing an aromatic thermotropic liquid crystal polyester, wherein the aromatic thermotropic liquid crystal polyester is synthesized using a boron-containing Lewis acid catalyst system, wherein the boron-containing Lewis acid catalyst system uses a boron-containing Lewis acid catalyst; during the synthesis, after mixing the aromatic monomer raw material with the boron-containing Lewis acid catalyst system, nitrogen is first introduced into the reaction system until the reaction system is in a nitrogen atmosphere, and then the reaction system is heated, and finally the reaction system is vacuum-reacted at 290 to 350° C. for 1 to 24 hours to obtain the aromatic thermotropic liquid crystal polyester. On the one hand, the synthesis method of the present invention is simple to operate, the reaction conditions are easy to control, the production cycle is short, and continuous production can be carried out without causing pollution to the environment; on the other hand, the aromatic thermotropic liquid crystal polyester obtained by the present invention has a high molecular weight, low dielectric loss, high tensile modulus, and a maximum tensile stress of up to 180 N / m 2 .

[0025] Compared with the existing technology of using metal catalysts or base catalysis to prepare liquid crystal polyesters, the present invention uses a boron-containing Lewis acid catalytic system. Not only does it have no metal residue in the product and is environmentally friendly, it also overcomes the shortcomings of base catalysis such as the effect of carboxylic acid monomers, providing a new catalytic system for the large-scale industrial continuous production of aromatic thermotropic liquid crystal polyesters.

[0026] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, to the extent such concepts are not mutually inconsistent, can be considered to be part of the inventive subject matter of this disclosure.

[0027] The foregoing and other aspects and features of the present invention will be more fully understood from the following description in conjunction with the embodiments. Other additional aspects of the present invention, such as features and / or beneficial effects of the exemplary embodiments, will become apparent from the following description or through practice of specific embodiments according to the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs.

[0029] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "a", "an" or "the" and similar words do not indicate a quantity limitation, but rather indicate the presence of at least one. Words such as "include" or "comprises" mean that the elements or objects appearing before "include" or "comprises" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.

[0030] Liquid crystal polyesters have a wide range of applications in polymer materials, communication technology, electronic devices, optical components, and other fields due to their low dielectric constant, low dielectric loss, and excellent overall performance. However, the metal catalyst systems or base catalyst systems used in the prior art for preparing liquid crystal polyesters may have problems such as metal residues in the products or the catalyst affecting the carboxylate functional groups of the raw materials, resulting in high production costs and low yields of liquid crystal polyesters. Therefore, the present invention aims to propose a method for synthesizing aromatic thermotropic liquid crystal polyesters to address the defects of the existing catalytic systems used in preparing liquid crystal polyesters.

[0031] Specifically, the present invention discloses a method for synthesizing an aromatic thermotropic liquid crystal polyester using a boron-containing Lewis acid catalyst system to synthesize the aromatic thermotropic liquid crystal polyester. Specifically, the method comprises the following steps: after mixing an aromatic monomer raw material with the boron-containing Lewis acid catalyst system, first passing nitrogen gas through the reaction system for 10 to 30 minutes, then subjecting the reaction system to a multi-stage temperature increase treatment, and finally subjecting the reaction system to a vacuum reaction at 290 to 350° C. for 1 to 24 hours to obtain the aromatic thermotropic liquid crystal polyester. The multi-stage temperature increase treatment of the reaction system comprises the following steps: first raising the temperature to 160 to 200° C. and maintaining the temperature for 10 minutes to 1 hour, then raising the temperature to 200 to 220° C. and maintaining the temperature for 1 to 2 hours, then raising the temperature to 240 to 260° C. and maintaining the temperature for 10 minutes to 1 hour, then continuing to raise the temperature to 270 to 290° C. and maintaining the temperature for 10 minutes to 1 hour, and finally raising the temperature to the vacuum reaction temperature.

[0032] In the above method, the amount of the boron-containing Lewis acid catalyst in the boron-containing Lewis acid catalytic system is 0.01 to 20 wt% of the total mass of the aromatic monomer raw material in the reaction system, and the mass of the aromatic monomer raw material in the reaction system is 1 to 200 g;

[0033] In a specific implementation, the aromatic monomer raw material is selected from bifunctional or multifunctional aromatic esters, aromatic acids, and aromatic alcohols, for example, two or three of the following aromatic monomers:

[0034]

[0035] The boron-containing Lewis acid catalytic system uses a boron-containing Lewis acid catalyst, and the boron-containing Lewis acid catalyst is selected from one or more of boric acid, boric acid esters, monosubstituted arylboronic acid, polysubstituted arylboronic acid, monosubstituted borane, and polysubstituted borane, for example, one or more of the following boron-containing Lewis acid catalysts:

[0036]

[0037]

[0038] The following is a further detailed description of the synthesis method of the aromatic thermotropic liquid crystal polyester disclosed in the present invention with reference to specific examples. In each example, the total mass of the aromatic monomer raw material is 100 g.

[0039] Example 1

[0040] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Boric acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 150 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0041] Example 2

[0042] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization kettle at a molar ratio of 4:1. Diboron pinacol diborate was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 165 N / m. 2Aromatic thermotropic liquid crystal polyester.

[0043] Example 3

[0044] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Bis(bis)-pyrocatechol borate was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 150 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0045] Example 4

[0046] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Phenylboric acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 180 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0047] Example 5

[0048] Methyl terephthalate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. P-fluorophenylboric acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 170 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0049] Example 6

[0050] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Trifluoromethylphenylboronic acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 110 N / m.2 Aromatic thermotropic liquid crystal polyester.

[0051] Example 7

[0052] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. 3,5-trifluoromethylphenylboronic acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 100 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0053] Example 8

[0054] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Triphenylborane was added as a catalyst and nitrogen was introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 90 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0055] Example 9

[0056] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor in a molar ratio of 4:1. Tris(pentafluorophenyl)borane was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 120 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0057] Example 10

[0058] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Boric acid was added as a catalyst and nitrogen was introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 80 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0059] Example 11

[0060] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Phenylboric acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 180 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0061] Example 12

[0062] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Trifluoromethylphenylboronic acid was added as a catalyst. Nitrogen was introduced for 20 minutes, and the temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 180 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0063] Example 13

[0064] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. 3,5-trifluoromethylphenylboronic acid was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 120 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0065] Example 14

[0066] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Pyridineboric acid was added as a catalyst and nitrogen was introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 150 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0067] Comparative Example 1

[0068] Methyl terephthalate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Nitrogen was introduced for 20 minutes without a catalyst. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 50 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0069] Comparative Example 2

[0070] Methyl benzoate and 6-(methoxycarbonyl)-2-naphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Magnesium acetate was added as a catalyst and nitrogen was introduced for 20 minutes. The temperature was then raised to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 100 N / m. 2 Aromatic thermotropic liquid crystal polyester.

[0071] Comparative Example 3

[0072] Methyl benzoate and hydroxynaphthoic acid were added to a polymerization reactor at a molar ratio of 4:1. Lanthanum trifluoromethanesulfonate was added as a catalyst. Nitrogen was first introduced for 20 minutes. The temperature was then programmed to rise to 180°C for 0.5 hours, then to 210°C for 1 hour, then to 250°C for 0.5 hours, then to 280°C for 0.5 hours, and finally to 300°C. The reaction system was allowed to react under vacuum at 300°C for 1 hour. The resulting polymer was quickly placed in deionized water and dried. The maximum tensile stress achieved was 110 N / m. 2Aromatic thermotropic liquid crystal polyester.

[0073] Based on the above examples 1-14 and comparative examples 1-3, it can be seen that the method for synthesizing aromatic thermotropic liquid crystal polyesters using a boron-containing Lewis acid catalyst system proposed in the present invention has a tensile stress of 50 N / m compared to that of aromatic thermotropic liquid crystal polyesters prepared without using a catalyst. 2 Increased to a maximum of 180N / m 2 , analysis found that the most likely reason for the increase in tensile stress is that the aromatic thermotropic liquid crystal polyester prepared by this scheme has a higher molecular weight and the product is more uniform; compared with the metal catalyst system, the present invention can also achieve the enhancement of the tensile properties of the aromatic thermotropic liquid crystal polyester under the same reaction conditions, and the synthesis method of the scheme of the present invention is simple to operate, the reaction conditions are easy to control, the production cycle is short and continuous production can be carried out without causing pollution to the environment.

[0074] While the present invention has been disclosed above with reference to preferred embodiments, this is not intended to limit the present invention. Persons skilled in the art will readily appreciate that various modifications and variations can be made without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A method for synthesizing an aromatic thermotropic liquid crystal polyester, characterized in that: Aromatic thermotropic liquid crystal polyesters were synthesized using a boron-containing Lewis acid catalytic system. The boron-containing Lewis acid catalytic system adopts a boron-containing Lewis acid catalyst, and the boron-containing Lewis acid catalyst is selected from one or more of boric acid, boric acid ester, monosubstituted aryl boronic acid, polysubstituted aryl boronic acid, monosubstituted borane, and polysubstituted borane.

2. The method for synthesizing the aromatic thermotropic liquid crystal polyester according to claim 1, characterized in that: After the aromatic monomer raw material is mixed with the boron-containing Lewis acid catalyst system, nitrogen is first introduced into the reaction system for 10 to 30 minutes, and then the reaction system is subjected to multi-stage temperature increase treatment, and finally the reaction system is subjected to vacuum reaction at 290 to 350° C. for 1 to 24 hours to obtain an aromatic thermotropic liquid crystal polyester; The process of multi-stage temperature treatment of the reaction system is as follows: first, the temperature is raised to 160-200°C and kept for 10 min-1 h, then the temperature is raised to 200-220°C and kept for 1-2 h, then the temperature is raised to 240-260°C and kept for 10 min-1 h, then the temperature is raised to 270-290°C and kept for 10 min-1 h, and finally the temperature is raised to the vacuum reaction temperature.

3. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The amount of the boron-containing Lewis acid catalyst in the boron-containing Lewis acid catalyst system is 0.01 to 20 wt % of the total weight of the aromatic monomer raw material in the reaction system.

4. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The aromatic monomer raw material is selected from bifunctional or multifunctional aromatic esters, aromatic acids and aromatic alcohols.

5. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The aromatic monomer raw material is selected from two or three of the following aromatic monomers:

6. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 1, characterized in that: The boron-containing Lewis acid catalyst is selected from one or more of the following boron-containing Lewis acid catalysts:

7. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The temperature of the reaction system for vacuum reaction is 300°C.

8. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The vacuum reaction time of the reaction system is 6 to 12 hours.

9. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The reaction system was subjected to vacuum reaction for 1 h.

10. The method for synthesizing aromatic thermotropic liquid crystal polyester according to claim 2, characterized in that: The mass of the aromatic monomer raw material in the reaction system is 1 to 200 g.

Citation Information

Patent Citations

  • Liquid crystal polymer composition

    CN107236265A

  • Liquid crystal polyester resin

    CN111825833A

  • Method for producing liquid-crystalline resin

    CN112334508A

  • Liquid crystal polyester as well as preparation method and application thereof

    CN116813893A

  • Alloy film for flexible circuit board and preparation method and application thereof

    CN118085544A